Glioma Cell Invasion Is Dependent Upon the DNA Damage Response Kinase ATR. (1st October 2022) - Birch, Joanna; Strathdee, Karen; Derby, Sarah; Koessinger, Anna; Chalmers, Anthony; Norman, Jim; Carruthers, Ross
Abstract: AIMS: Gliomas have high levels of DNA replication stress and clinical trials of inhibitors of the key replication stress response protein ATR (ataxia telangiectasia and rad 3 related protein) as radiosensitisers are planned. We aimed to investigate the effect of ATR inhibition on the ability of glioma cells to infiltrate and invade the brain. METHOD: Live cell imaging in a panel of primary glioma cultures following siRNA or pharmacological inhibition of ATR. Invasion following treatment of murine orthotopic gliomas was determined by immunohistochemistry. Intravital imaging of GFP expressing murine orthotopic xenografts via an intracranial window model of glioma was undertaken. RESULTS: Invading margins of human glioma samples demonstrated increased pATR expression relative to core. Live cell imaging demonstrated reduced cell velocity following ATR inhibition (Berzosertib/BAY1895344) or siRNA. Cytoplasmic vacuolation occurred following ATRi or siRNA which were single walled structures which engulf high molecular weight dextran, compatible with blockade of macropinosome processing. Live cell imaging with GFP-integrin α5 and integrin recycling assays showed sequestration of integrins within macropinosomes and reduced integrin cycling. Intravital in vivo imaging of murine xenograft tumours confirmed vacuolation and dextran uptake following ATRi, whilst a further in vivo study demonstrated a reduction in invading tumour cells. CONCLUSION: We demonstrate a novel role for ATR in facilitating macropinocytic vesicle trafficking and integrin recycling in GBM cells which results in a profound motility defect in vitro and in vivo. ATR inhibitors are entering early phase trials as radiation sensitisers and we propose that therapeutic benefit will extend beyond DNA damage potentiation.